Aggregate dynamics in a large virtual economy: Prices and real activity in Team Fortress 2 - Matt Baumer; Curtis Kephart (University of California, Economics Department, 2015)
We examine economic activity in a large virtual economy which was designed to allow decentralized barter as the sole exchange institution. We find that a small subset of goods emerges endogenously which act of media of exchange. Our analysis includes estimation of spot exchange rates between these numerous money goods and we develop methods which allows us to price all goods and track inflation. We then calculate nominal growth and its components. We find that per-captita real wealth is an increasing component of nominal growth. Separately, we find evidence of a certain form of nominal price ridigity - the price of an item commonly priced in a particular money good tends to move with the exchange rate of that money good. We also find that announcements made by the economic planners can induce speculation leading to localized asset price bubbles.
Keywords: E01; E31; P44; 330; virtual economy; barter system; national income accounting; wealth measurement; price level; inflation